Crack growth analysis in reinforced concrete using BEM - Saleh, Abdul Latif; Aliabadi, MH (American Society of Civil Engineers, 1998)
A boundary-element formulation for modeling the nonlinear behavior of reinforced concrete is presented. The influence of reinforcements on the concrete is considered as a distribution of forces over the region of attachment. The solution for the attachment forces is obtained from the condition that the deformations of the concrete and the reinforcement under the action of the external loading are compatible. The yielding of reinforcement is considered when the total force at any section of the reinforcement is greater than the yielding force and is assumed to be broken when the strain reaches the maximum strain. The fracture of concrete is simulated using the fictitious crack model in which the fracture zone is replaced by closing forces acting on both crack surfaces. In using the boundary-element method to simulate cracks, the crack path is not known in advance because it can be calculated during the iteration process, and then the need of remeshing becomes obsolete. The numerical results obtained are compared to the finite-element method analysis and experimental results.